Simultaneous Determination of Environmental Endocrine Disruptors in Environmental Water by Gas Chromatography-Flame Ionization Detector - Wang1, Bo; Wang2, Xiaolin; Lin2, Huaping; Li3, Chengyao; Zhu4, Hai; Bi3, Siyuan; Lian2, Kaoqi (Asian Journal of Chemistry, 2014)
A sensitive and selective method using gas chromatography-flame ionization detector (GC-FID) for analysis of 4-nonylphenol, bisphenol A, estradiol and estriol in aqueous environmental samples. The targets extracted by solid-phase extraction using Oasis HLB cartridges and derivatized with N,O-bis (trimethylsilyl) acetamide. The optimization of operating conditions influencing the performances of solid-phase extraction and derivatization were studied. Calibration curves were linear in the range of 20 to 1000 ng L-1 for endocrine disruptors and the limit of detection (LOD) and limit of quantitation (LOQ) were in the range 3.6-6.4 ng L-1 and 12.4-19.8 ng L-1, respectively. The results of recovery indicated that the method had good precision and reproducibility. The established method was successfully applied to determination of the target exogenous compounds in man-made river waters in Shijiazhuang, China.